(untitled) (Mustansiria Dental Journal, 2018)
Acrylic resin is the most widely used material in prosthetic dentistry and its dimensional accuracy is most important factor in successfulness denture constructer. The aim of this study was to investigate the dimensional changes of denture base acrylic cured by long and short curing method by using conventional water bath. 60 maxillary wax bases were made and randomly assigned in 3 groups specimens according to the stringy, dough like and rubbery stages of the acrylic resin cured by: 1-long curing cycle: curing the resin at 74 C° for 9 hours. 2-Short curing cycle: processing the resin at 74 C° for 1 1/2 hour and at 100 C° for 1/2 hour. Results were submitted to ANOVA and Turkey’s test and it showed that in short curing cycle, the dough like stages presented values (0.193 mm) with statistically significant difference (P<0.05) when compared with the stringy (0.246mm) and rubbery (0.240 mm) stages. While for the long curing cycle the dough stage presented values (0.199mm) with statistically significant difference (P<0.05)when compared with stringy (0.230mm) and rubbery (0.239mm) St